(untitled) (International Journal of Engineering and Computer Science, 2017)
The rapid growth in infrastructure and industrial plants creating environmental issues like climate change, malfunctioning and pollution. The project shows the estimated values of environmental parameters by using the adaptable and smart monitoring systems. The solution includes the technology Internet of Things (IoT).The existing model describes the original value of the environmental parameters with the help of the sensor networks. The proposed model comprises of lcd displays or alarms which displays the exceeded value of the environmental parameters .The implementation is tested for CO2,noise,temperature,humidity,acid rain detection in rain